Delegation and Incentive Compensation - Nagar, Venky (The Accounting Review, 2002)
Top management faces two key organizational design choices: (1) how much authority to delegate to lower-level managers, and (2) how to design incentive compensation to ensure that these managers do not misuse their discretion. Theoretical accounting literature emphasizes that top management makes these two choices jointly, but there is little empirical evidence on this assertion. Capitalizing on a unique database of branch manager practices in retail banks, this study provides some of the first evidence on the joint nature of the delegation and incentive compensation choices for lower-level managers. A simultaneous model of these two choices indicates that high-growth, volatile, and innovative banks delegate more authority to branch managers. In turn, branch managers with more authority receive more incentive-based pay. However, in contrast with principal-agent theory, I find no evidence that the extent of incentive compensation plays a significant role in explaining the extent of delegation.